Experimental Carotid Stenosis and Endothelial Injury in the Rabbit: An In Vivo Model to Study Intravascular Platelet Aggregation - Golino, Paolo; Ambrosio, Giuseppe; Pascucci, Immacolata; Ragni, Massimo; Russolillo, Enrico; Chiariello, Massimo (Thrombosis and Haemostasis, 1992)
Previous studies have shown that experimental canine coronary artery stenosis associated with endothelial injury results in a typical pattern of coronary flow characterized by gradual decreases in coronary flow to almost zero values followed by restorations of flow to normal values. This pattern of flow, called cyclic flow reductions (CFRs), is the consequence of recurrent platelet aggregation at the site of the stenosis and endothelial injury and subsequent dislodgement of the thrombus. In the present study, platelet activation and aggregation in vivo was induced by placing an external constrictor around carotid arteries with endothelial injury in anesthetized rabbits. Carotid blood flow velocity was measured continuously with a Doppler flow probe positioned proximally to the constrictor. After placement of the constrictor, CFRs developed in 14 of 14 rabbits with a mean frequency of 16.5 ± 2.3 cycles/h. CFRs were observed for 30 min, and the animals were treated with either an i.v. bolus of aspirin (10 mg/kg) or R 68070 (20 mg/kg), a drug with simultaneous TxA2 synthase and TxA2/PGH2 receptor blocking properties. Aspirin completely inhibited CFRs in 4 of 7 rabbits, whereas R 68070 eliminated CFRs in 7 of 7 animals. In the 3 animals that did not respond to aspirin, administration of ketanserin (0.25 mg/ kg i.v.), a selective serotonin S2 receptor antagonist, completely abolished CFRs. Both aspirin and R 68070 resulted in a marked reduction in serum TxB2 formation and in a complete inhibition of ex vivo platelet aggregation in response to arachidonic acid, whereas aggregation in response to U46619, a TxA2 mimetic, was inhibited only in R 68070-treated rabbits. We conclude that 1) CFRs develop in rabbit carotid arteries at sites of experimental stenosis and endothelial injury; 2) this model can be usefully employed to study platelet aggregation and platelet-vessel wall interaction in vivo and to test the efficacy of antiplatelet interventions.